Do glia provide the link between low‐grade systemic inflammation and normal cognitive ageing? A 1H magnetic resonance spectroscopy study at 7 tesla. Issue 1 (14th July 2021) - Lind, Anna; Boraxbekk, Carl‐Johan; Petersen, Esben Thade; Paulson, Olaf Bjarne; Andersen, Ove; Siebner, Hartwig Roman; Marsman, Anouk
Abstract: Low‐grade systemic inflammation contributes to ageing‐related cognitive decline, possibly by triggering a neuroinflammatory response through glial activation. Using proton magnetic resonance spectroscopy ( 1 H‐MRS) at 7T in normal human individuals from 18 to 79 years in a cross‐sectional study, we previously observed higher regional levels of myo‐inositol (mIns), total creatine (tCr) and total choline (tCho) in older than younger age groups. Moreover, visuo‐spatial working memory (vsWM) correlated negatively with tCr and tCho in anterior cingulate cortex (ACC) and mIns in hippocampus and thalamus. As mIns, tCr and tCho are higher in glia than neurons, this suggest a potential in vivo connection between cognitive ageing and higher regional levels of glia‐related metabolites. In the present study, we tested whether these metabolic differences may be related to low‐grade systemic inflammation. In the same individuals, plasma concentrations of the proinflammatory markers C‐reactive protein (CRP), interleukin 8 (IL‐8), and tumour necrosis factor α (TNF‐α) were measured on the same day as 1 H‐MRS assessments. We tested whether CRP, IL‐8, and TNF‐α concentrations correlated with the levels of glia‐related metabolites. CRP and IL‐8, but not TNF‐α, were higher in older (69–79 years) than younger (18–26 years) individuals. CRP correlated positively with thalamic mIns and negatively with vsWM. IL‐8 correlated positively with ACC tCho and hippocampal mIns, but not with vsWM. Mediation analysis revealed an indirect effect of IL‐8 on vsWM via ACC tCho. Together, these findings corroborate the role of glial cells, perhaps via their role in neuroinflammation, as part of the neurobiological link between systemic inflammation and cognitive ageing. Abstract : Systemic inflammation contributes to ageing‐related cognitive decline, possibly by triggering a neuroinflammatory response through glial activation. Using magnetic resonance spectroscopy, we previously observed higher glia‐related metabolite levels in older than younger human individuals. Working memory was correlated with prefrontal, hippocampal and thalamic glia‐related metabolite levels. The current study shows that concentrations of proinflammatory markers are higher in older than younger individuals and correlate with prefrontal, hippocampal and thalamic glia‐related metabolite levels. Proinflammatory markers may have an indirect effect on working memory via glia‐related metabolites. Glial cells may thus be part of the neurobiological link between systemic inflammation and cognitive ageing.